Rich Extract On Total Polyphenols And Antioxidant Activity Obtained By Conventional And Non-conventional Methods From Ahmeur Bouamer Grape Seed - Ghouila, Z.; Laurent, S.; Henoumont, C.; Vander Elst, L.; Muller, R. N.; Baaliouamer, A. (University of Eloued جامعة الوادي, 2016)
Conventional and non-conventional extraction methods were applied in the first time for the determination of total polyphenols from Ahmeur Bouamer, an anthoctonous variety grape seeds. Independently of the time and temperature, a positive effect of particle size parameter on maceration has been noted and relativly high concentrations in polyphenols for 500 μm (67.78 ± 0.46 mg GAE/gdm), 500-355 μm (90.95 ± 0.24 mg GAE/gdm) and 355-180 µm (114.82 ± 1.24 mg GAE/gdm) have been obtained. The higher value of yield was reached by the microwave extraction (37.74±0.32%), followed by the maceration (14.16±0.15%) and the ultrasound (6.70±0.25%). The appropriate extraction method to obtain a relatively strong antioxidant activity from seeds was the microwave with inhibition of 69.67±1.76 % and 78.05±2.05% of DPPH and ABTS+ free radicals, respectively.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 03
Keywords: Ahmeur Bouamer, extraction, grape seeds, total polyphenols, antioxidant activity.